Association between Radiological Response after Locoregional Treatment and Histopathological Findings in Patients Undergoing Liver Transplant for Hepatocarcinoma - Mohamed Hassin Mohamed Chairi; Ana Belén Vico Arias; Natalia Zambudio Carroll; María Trinidad Villegas Herrera; Jesús María Villar del Mora (Indian Journal of Transplantation)
Introduction: Liver Imaging Reporting and Data System treatment response (LR-TR) algorithm have been developed to evaluate response after locoregional therapy (LRT) in patients with hepatocellular carcinoma (HCC). The aim of the study was to corroborate if the posttreatment radiological findings described using LR-TR correspond to the final histopathological results, and survival in relation to different LR-TR groups in patients who underwent LRT before liver transplantation (LT). Materials and Methods: A retrospective single-center study was performed. Data of patients undergoing LT due to HCC between January 2010 and December 2022 were collected, selecting patients who underwent LRT. Results: Four hundred and four patients were transplanted, of which 103 (25.5%) had HCC. Ninety-seven (93.2%) patients received LRT. Fifty-three percent of treated patients had a complete response on pathological examination. Re-evaluation imaging was performed in 88 patients. Fifty-nine percent were classified as nonviable LR-TR, 32.5% as viable LR-TR, and 8.5% as equivocal LR-TR. Regarding the correlation between the degree of tumor necrosis and the posttreatment LR-TR category, 37% of patients evaluated as viable LR-TR had a “complete response” compared to 62.9% with “no complete response.” For those evaluated as nonviable LR-TR, 59.2% had a “complete response” compared to 40.8% with “no complete response” (P = 0.123). There were no statistically significant differences in overall and disease-free survival between the viable LR-TR, nonviable LR-TR, and equivocal LR-TR groups (P = 0.3484 and P = 0.4152, respectively). Conclusions: We have not been able to establish whether radiological response correlates with anatomopathological outcomes, as well as survival in these groups. More prospective studies are needed to validate these findings.